2011
DOI: 10.1021/es200812e
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Processing Potential in Prairie Pothole Porewaters

Abstract: Prairie pothole lakes (PPLs) are located within the extensively farmed Great Plains region of North America, and many are negatively impacted by nonpoint source pesticide pollution. To date, the environmental fate of pesticides in these lakes remains largely unknown. In this study, two PPLs in the Cottonwood Lake area of North Dakota were sampled, and transformations of four chloroacetanilide pesticides in sediment porewaters were examined. The reduced sulfur species in the porewaters, such as bisulfide (HS(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 56 publications
(115 reference statements)
1
66
0
Order By: Relevance
“…Abiotic transformation of the antibiotics might contribute a great to the degradation during composting. Research has demonstrated that high-organic soils/sediments tend to produce elevated levels of reduced sulfur compounds (e.g., bisulfide and polysulfides) and iron(II) species, which typically possess strong reducing capacity that may degrade veterinary antibiotics faster than microorganisms (Zeng et al 2011(Zeng et al , 2012Mohatt et al 2011). Similar to the manures, the SAs concentrations in the composts are lower than other TCs and FQs generally; however, SDZ in the soybean meal compost (SMC) and SCX in the rice husk compost (RHC) are prominent due to their significant higher level in the two composts.…”
Section: Veterinary Antibiotic Residues In Compostsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic transformation of the antibiotics might contribute a great to the degradation during composting. Research has demonstrated that high-organic soils/sediments tend to produce elevated levels of reduced sulfur compounds (e.g., bisulfide and polysulfides) and iron(II) species, which typically possess strong reducing capacity that may degrade veterinary antibiotics faster than microorganisms (Zeng et al 2011(Zeng et al , 2012Mohatt et al 2011). Similar to the manures, the SAs concentrations in the composts are lower than other TCs and FQs generally; however, SDZ in the soybean meal compost (SMC) and SCX in the rice husk compost (RHC) are prominent due to their significant higher level in the two composts.…”
Section: Veterinary Antibiotic Residues In Compostsmentioning
confidence: 99%
“…Thus, some degradation of antibiotics is likely to occur during the composting, especially during the exothermic stage (Kim et al 2012). Meanwhile, abiotic reaction with reduced sulfur species could remove the antibiotics from the fresh manures during composting (Zeng et al 2011(Zeng et al , 2012. The objectives of the present study were therefore to identify veterinary antibiotic residues in animal manures and different types of compost and to evaluate the ecological risks associated with the application of organic fertilizers in the protected vegetable farming based on the observed concentrations of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic reduction reactions have been reported to be an important removal pathway for chemicals in subsurface environments due to the presence of reduced sulfur compounds (e.g., bisulfide and polysulfides) in soils and associated pore waters (Zeng et al, 2011;Zeng et al, 2012). Sorption-desorption processes play an important role in understanding the bioavailability of chemicals in soil (Tolls, 2001;Huang et al, 2003;Kümmerer, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Boxall et al (2004) discuss the risks to the environment from a range of veterinary medicines. Pesticides have been detected at trace concentrations in groundwater worldwide since the 1980s and remain important contaminants (Arias-Estévez et al, 2008;Baran et al, 2008a;Close, 1996;Gilliom, 2007;Kolpin et al, 2000;Tappe et al, 2002;Walls et al, 1996;Zeng et al, 2011). The problem of persistent transformation products produced from partial degradation of pesticides in groundwater has also been recognised (Galassi et al, 1996;Somasundaram and Coats, 1991) and a wide range of such products have been identified in groundwater (e.g.…”
Section: Introductionmentioning
confidence: 99%